The Security Picalculus and Non-interference. - HENNESSY, MATTHEW (Elsevier, 2005)
The security -calculus is a typed version of the asynchronous -calculus in which the types, in addition to constraining the input/output behaviour of processes, have security levels associated with them. This enables us to introduce a range of typing disciplines which allow input or output behaviour, or both, to be bounded above or below by a given security level. We define typed versions of may and must equivalences for the security -calculus, where the tests are parameterised relative to a security level. We provide alternative characterisations of these equivalences in terms of actions in context ; these describe the actions a process may perform, assuming the observer is constrained by a given typing environment. Using these alternative characterisations we prove non-interference results with respect to may and must testing. These show that information flow between security levels can be controlled using our typing systems.
PUBLISHED
Keywords: Computer science; Distributed Systems; picalculus; security types; non-interference; testing equivalences